The Eastern Arc Mountains and coastal forests of East Africa—an archive to understand large-scale biogeographical patterns: Pseudotomias, a new genus of African Pseudophyllinae (Orthoptera: Tettigoniidae) - Hemp, Claudia (Zootaxa, 2016)
A new genus of Pseudophyllinae restricted to East Africa is described. Data on the ecology, and the habitat are provided. The biogeographical pattern and morphology suggests an old radiation since Tomias from Central and West Africa is the closest relative to Pseudotomias. The old forests of East Africa could hereby be the source of representatives of this old radiation since venation is less reduced in East African taxa of Phyllomimini.